Optic nerve compression and retinal degeneration in Tcirg1 mutant mice lacking the vacuolar-type H-ATPase a3 subunit. - Nobuyuki Kawamura; Hiroyuki Tabata; Ge-Hong Sun-Wada; Yoh Wada (PLoS ONE, 2010)
BACKGROUND: Vacuolar-type proton transporting ATPase (V-ATPase) is involved in the proper development of visual function. Mutations in the Tcirg1 (also known as Atp6V0a3) locus, which encodes the a3 subunit of V-ATPase, cause severe autosomal recessive osteopetrosis (ARO) in humans. ARO is often associated with impaired vision most likely because of nerve compression at the optic canal. We examined the ocular phenotype of mice deficient in Tcirg1 function. METHODOLOGY/PRINCIPAL FINDINGS: X-ray microtomography showed narrowed foramina in the skull, suggesting that optic nerve compression occurred in the a3-deficient (Tcirg1-/-) mice. The retina of the mutant mice had normal architecture, but the number of apoptotic cells was increased at 2-3 wks after birth. In the ocular system, the a3 subunit accumulated in the choriocapillary meshwork in uveal tissues. Two other subunit isoforms a1 and a2 accumulated in the retinal photoreceptor layer. We found that the a4 subunit, whose expression has previously been shown to be restricted to several transporting epithelia, was enriched in pigmented epithelial cells of the retina and ciliary bodies. The expression of a4 in the uveal tissue was below the level of detection in wild-type mice, but it was increased in the mutant choriocapillary meshwork, suggesting that compensation may have occurred among the a subunit isoforms in the mutant tissues. CONCLUSIONS: Our findings suggest that a similar etiology of visual impairment is involved in both humans and mice; thus, a3-deficient mice may provide a suitable model for clinical and diagnostic purposes in cases of ARO.